Management issues in ecological problems of tourism industry in Odessa - Marshalenko, Marianna (My University, 2018)
Issues of management of ecological problems of tourism industry in Odessa are disclosed.
Keywords: туризм; екологія; Одеса; кафедра готельно-ресторанної справи; экология; Одесса; tourism; ecology; Odessa